Pengaruh Model Problem Based Learning (PBL) Menggunakan Lembar Kerja Peserta Didik Elektronik (E-LKPD) Terhadap Hasil Belajar Biologi Siswa Kelas X Di SMAN 2 Langsa: (The Influence of Problem Based Learning (PBL) Model Using E-LKPD on Biology Learning Outcomes of Grade X Students at SMAN 2 Langsa) - Sitakar, Sahna Maulana; Elfrida , Elfrida; Sarjani , Tri Mustika (BIODIK, 2025)
This study aims to determine the effect of the Problem Based Learning learning model using Electronic Student Worksheets on the biology learning outcomes of class X students at SMAN 2 Langsa. This study uses a quantitative research type with the True Experimental Design method with a pretest-posttest control group design. The sample of this study was class XD and XE students of SMAN 2 Langsa with a total of 58. The results of the study indicate that there is a significant effect of the application of the Problem Based Learning model using Electronic Student Worksheets on student learning outcomes, as evidenced by the hypothesis test which shows a sig. (2-tailed) = 0.002 <α = 0.05, so H1 is accepted and H0 is rejected. This means that the application of the Problem Based Learning model using Electronic Student Worksheets has an effect on student learning outcomes. The magnitude of the effect is indicated by the effect size value d = 0.857, which is included in the category of having a large effect, on the biology learning outcomes of class X students at SMAN 2 Langsa. This is due to the variation of learning models, with the application of the Problem Based Learning model using Electronic Student Worksheets whose interactivity and accessibility are presented digitally including materials, videos, images, and questions discussed in groups. This encourages students to think actively and collaborate, so that students can understand the lessons and answer questions optimally. In addition, the available facilities such as Wi-Fi, computers, and mobile phones also support this learning. Abstrak. Penelitian ini bertujuan untuk mengetahui pengaruh model pembelajaran Problem Based Learning (PBL) yang menggunakan Lembar Kerja Peserta Didik Elektronik (E-LKPD) terhadap hasil belajar biologi siswa kelas X di SMAN 2 Langsa, serta untuk mengukur seberapa besar pengaruh dari penerapan model tersebut terhadap hasil belajar siswa. Penelitian ini menggunakan jenis penelitian kuantitatif dengan metode True Experimental Design dengan desain pretest-posttest control group design. Sampel penelitian ini adalah siswa kelas XD dan XE SMAN 2 Langsa dengan jumlah 58. Hasil penelitian menunjukkan bahwa adanya pengaruh signifikan penerapan model Problem Based Learning (PBL) menggunakan E-LKPD terhadap hasil belajar siswa, terbukti dari uji hipotesis yang menunjukkan nilai sig. (2-tailed) = 0,02 < α = 0,05, sehingga H1 diterima  dan H0 ditolak. Besar pengaruhnya ditunjukkan oleh nilai effect size d = 0,857, yang termasuk dalam kategori berpengaruh besar, terhadap hasil belajar biologi siswa kelas X di SMAN 2 Langsa.